Alert Features for Healthcare in Increasing Hospital Revenue from DRG Reimbursement: A Systematic Literature Review - Maryati, Warsi; Utami, Yeni Tri; Muhtarom, Moch (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
The inadequate quality of medical records and theelevated rate of insurance claim denials worldwide havenecessitated the incorporation of alert functionalities intoElectronic Health Record (EHR) systems to enhancedocumentation precision and reimbursementeffectiveness. This research seeks to evaluate the impactof alerts on healthcare professionals' ability to enhancethe quality of medical records (completeness, accuracy,timeliness) and insurance claim results through aSystematic Literature Review (SLR) following PRISMA 2020guidelines. Out of 538 studies sourced from PubMed,Scopus, and Web of Science, 14 were selected based onstrict inclusion criteria. The synthesis of results reveals thatalerts—particularly those integrated with clinical decisionsupport—substantially enhance documentation qualityand decrease claim rejections. The successful execution ofthis integration relies on EHR compatibility, managementbacking, user education, and the alleviation of alertfatigue. These results offer an empirical foundation foroptimizing hospital revenue by improving the quality ofmedical records and the efficiency of claims, althoughadditional research is required in the contexts ofdeveloping countries and for evaluating cost-effectiveness.